EFEKTIVITAS EKSTRAK DAUN NANGKA (Artocarphus heterophyllus) UNTUK PENGOBATAN INFEKSI BAKTERI Aeromonas hydrophila PADA BENIH NILA SALIN (Oreochromis sp) - Anggita, Rina; AS, Agus Putra; Putriningtias, Andika (JURNAL PERIKANAN TROPIS, 2025)
Tilapia (Oreochromis sp) is a fishery commodity that is popular with the public because it has thick flesh and a delicious taste. This study aims to test the effectiveness of jackfruit (Artocarphus heterophylluis) leaf extract in treating Aeromonas hydrophila bacterial infections in salted tilapia seeds (Oreochromis sp). The research method used in the research was a Completely Randomized Design (CRD) method with 4 treatments and 3 replications. The treatments that will be carried out are PEN0 (Control) PEN1 (0.5 ml/L), PEN2 (1.5 ml/L) and PEN3 (2.0 ml/L). Parameters observed: Clinical symptoms, length of healing time, survival rate and water quality measurements. The results of the research were that the use of jackfruit leaf extract had an effect on the survival of salted tilapia (Oreochromis sp) seeds infected with Aeromonas hydrophila bacteria. The best survival rate for saline tilapia seeds (Oreochromis sp) was found in PEN3 (jackfruit leaf extract 2.0 ml/L) with a percentage of 83% and the lowest survival rate was found in PEN0 with a percentage of 0%.